Outcomes of patients treated with ultrathin-strut biodegradable polymer sirolimus-eluting stents versus fluoropolymer-based everolimus-eluting stents: A meta-analysis of randomised trials - Cassese, Salvatore; Ndrepepa, Gjin; Byrne, Robert A.; Kufner, Sebastian; Lahmann, Anna Lena; Mankerious, Nader; Xhepa, Erion; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Fusaro, Massimiliano; Kastrati, Adnan; Joner, Michael (EuroIntervention, 2018)
Aims: The ultrathin-strut biodegradable polymer sirolimus-eluting stent (SES) is a new-generation drug-eluting stent (DES) developed to improve the percutaneous treatment of patients with coronary artery disease. Here, we sought to investigate whether the performance of the ultrathin-strut biodegradable polymer SES is superior to that of the benchmark thin-strut fluoropolymer-based everolimus-eluting stent (EES). Methods and results: We undertook a study-level meta-analysis of trials in which patients receiving percutaneous coronary intervention (PCI) were randomly assigned to either SES or EES. Primary efficacy and safety outcomes were target lesion revascularisation (TLR) and definite/probable stent thrombosis (ST), respectively. Secondary outcomes were myocardial infarction (MI), death, target lesion failure (TLF) and target vessel failure (TVF). A total of 4,853 patients received a PCI with either SES (n=2,816) or EES (n=2,037) in six trials. After a weighted median follow-up of 12 months, patients treated with SES had a risk of TLR (odds ratio [95% confidence interval]: 1.24 [0.83-1.85], p=0.30), definite/probable ST (0.84 [0.53-1.33], p=0.45) and MI related to the target vessel (0.77 [0.55-1.07], p=0.12) comparable to that of patients treated with EES. We found no significant difference with regard to other secondary outcomes. Conclusions: At one-year follow-up, the ultrathin-strut biodegradable polymer sirolimus-eluting stent displays a performance comparable to that of the fluoropolymer-based everolimus-eluting stent.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Clinical research Clinical trials Drug-eluting stent